1989
DOI: 10.1016/0014-5793(89)81388-2
|View full text |Cite
|
Sign up to set email alerts
|

Zinc increases phorbol ester receptors in intact B‐cells, neutrophil polymorphs and platelets

Abstract: In the presence of pyrithione, which was used as a Zn *+ ionophore, Znzf (l&l00 PM) increased phorbol ester binding by intact B-CLL cells in a dose-dependent fashion. Zn pyrithione increased 2-fold the number of phorbol ester receptors in B-cells (0.74 to 1.4 pmol/lV cells), neutrophil polymorphs (0.2 to 0.51 pmol/lW cells) and platelets (91 to 209 pmol/lOiO cells). Fractionation of cells after treatment with Zn pyrithione showed that increased binding of PDBu occurred in the particulate fraction of cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…5). Zn2+ is incorporated into synaptic terminals (35) and induces PKC translocation in several cells (36,37). Indeed, we found that addition of Zn2+ to guinea pig cerebral homogenate induced translocation of PKC in a dose-dependent manner (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…5). Zn2+ is incorporated into synaptic terminals (35) and induces PKC translocation in several cells (36,37). Indeed, we found that addition of Zn2+ to guinea pig cerebral homogenate induced translocation of PKC in a dose-dependent manner (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…We have used the zinc-ionophore, pyrithione (Pyr), which forms a 2:1 (ligand:metal) hydrophobic complex and shuttles zinc across membranes down a concentration gradient. 13 To follow the influx of zinc into cells we loaded brain slices with the acetoxymethyl (AM) ester form of the zinc-sensitive indicator FluoZin-3 14 that leads to accumulation of the probe intracellularly. Application of the membrane impermeant chelator Ca-EDTA 15 leads to a small reduction in the signal confirming that most of the signal arises from intracellularly entrapped probe (Figure 3).…”
Section: ■ Resultsmentioning
confidence: 99%
“…209 The elevation of an electron from HOMO to LUMO upon photo-excitation leads to the change of dipole moment. The DFT calculation of FMOs usually agrees with the qualitative conclusion drawn from analyzing the resonance structures, as shown in Fig.…”
Section: Singlet State Ligand-centered Photophysical Processesmentioning
confidence: 99%
“…Pyrithione is a widely used ionophore for transporting Zn(II) ions in the form of [ZnL 2 ] to intracellular space. 209,210 Hydroxamates are potent Zn(II) protease inhibitors. 211 These compounds offer two oxygen donors which are hard Lewis bases (see below) and are also good ferric ion ligands.…”
Section: Zn(ii) Coordination Chemistrymentioning
confidence: 99%